An Improved Experimental Model of Hemorrhoids in Rats: Evaluation of Antihemorrhoidal Activity of an Herbal Formulation. (11th March 2014) - Azeemuddin, Mohammed; Viswanatha, Gollapalle Lakshminarayanashastry; Rafiq, Mohamed; Thippeswamy, Agadi HireMath; Baig, Mirza Rizwan; Kavya, Kethaganahalli Jayaramaiah; Patki, Pralhad Sadashiv; Shyam, Ramakrishnan
Abstract : Objective . To improve the existing experimental model of croton oil-induced hemorrhoids in rats by using Evans Blue (EB) dye extravasation technique. Further, an herbal formulation (Pilex) was evaluated for its antihemorrhoidal activity in this model. Methods . Two sets of experiments were carried out: first to improve the experimental model and to validate the same using Pilex and second to evaluate the effect of Pilex on cytoarchitecture of rectoanal tissue in croton oil-induced hemorrhoids. In both sets, hemorrhoids were induced to all the animals, except normal controls, by applying croton oil via rectoanal region and the effect of Pilex ointment (PO), Pilex granules (PG), and combination of PG and PO was evaluated. In the first set, extravasation of EB dye, TNF- α, IL-6, and rectoanal coefficient (RAC) was determined. In the second set, severity of score, RAC, and histopathology were evaluated. Results . The elevated levels of TNF- α, IL-6, and extravasations of EB dye were decreased with the Pilex treatment. The cytoarchitecture of rectoanal portion of the animals treated with Pilex was near to normal. Conclusion . The improved experimental model of hemorrhoid is useful in quantifying the inflammatory exudates and extent of inflammation. In this improved experimental model Pilex showed antihemorrhoidal activity, which further validates its clinical usage.